Metals in Soil - Contamination and Remediation 2019
DOI: 10.5772/intechopen.82770
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chemical Properties of Soil on the Corrosion Morphology of Carbon Steel Pipes

Abstract: Corrosive soils are responsible for the deterioration of buried underground utilities such as buried steel pipes. Frequent pipe failures are reported due to corrosive soil globally. Although soil's corrosion phenomenon has been understood and identified long time ago, pipe failures due to corrosive soil are uncontrollable and unavoidable despite the use of protective coatings and techniques such as cathodic protection. Therefore, it is essential to review the causes of soil's corrosivity for the protection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Meanwhile, from the minimum value of chloride concentration to the maximum value of sulfate concentration, the corrosion current density increased from 4.2 to more than 9 , which indicates quite a large influence. Several other studies have investigated this behavior and agree with these results [ 31 , 32 , 33 ].…”
Section: Resultssupporting
confidence: 82%
“…Meanwhile, from the minimum value of chloride concentration to the maximum value of sulfate concentration, the corrosion current density increased from 4.2 to more than 9 , which indicates quite a large influence. Several other studies have investigated this behavior and agree with these results [ 31 , 32 , 33 ].…”
Section: Resultssupporting
confidence: 82%
“…Marusic et al (2018) stated that corrosion in soils resembles atmospheric corrosion with corrosion rates usually higher and depending on the soil type [22]. In the next research, Wasim and Shoaib (2019) revealed that varying moisture and chloride contents can cause corrosion problems [35]. Accordingly, Liu et al (2019) argue that the corrosion is accelerated with the increasing soil thickness due to more water contained in the soil [20].…”
Section: The Effect Of Soil Engineering Properties On Corrosion (Litementioning
confidence: 99%
“…Another thing that is concerned about is the corrosion process of steel. Veleva et al [84]; Norhazilan et al [85]; Noor and Al-Moubaraki [86]; Lim et al [87]; Wasim and Shoaib [88]; Liu et al [89] revealed that soil composed of silt and clay will have the highest level of corrosion compared to soil composed of rough grains (gravel to sand), this is related to the water content, the corrosion process will be high in soils with high water content. Iqbal et al [29] stated that the properties of soil engineering (plasticity index, water content, and clay content) impact the corrosion process of steel.…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%